Pleural Effusion, Pneumothorax, and Lung Entrapment in Rheumatoid Arthritis. Issue 4 (June 2015) - Komarla, Ashwini; Yu, Gordon H.; Shahane, Anupama
<x xml:space="preserve">Abstract</x> Abstract Rheumatoid arthritis (RA)–associated pleural effusions are usually small and asymptomatic with no need for intervention, but complex and symptomatic rheumatoid pleural effusions may be seen and are associated with significant morbidity and mortality. Pleural effusions may develop before, concurrently with, or after the joint manifestations of RA. The classic features of RA-associated pleural effusions include high cell counts and protein, lipid, and lactate dehydrogenase levels and very low glucose levels, along with distinctive cytopathologic findings: slender spindle-shaped cells, multinucleated giant cells, eosinophilic granular debris, and the absence of mesothelial cells. Rarely, rheumatoid pleural involvement can include pneumothorax or can be severe enough to progress to lung entrapment, which may cause significant restrictive lung disease and require surgical therapy. Rheumatoid pleural involvement may not always correlate with joint activity but can be a significant cause of shortness of breath for patients with RA.